2009
DOI: 10.1016/j.juro.2009.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Prostate Cancer Risk in a Cohort of Veterans Undergoing Prostate Needle Biopsy

Abstract: To our knowledge these results provide the first evidence of an association between exercise and prostate cancer risk as well as grade at diagnosis in men scheduled to undergo prostate biopsy. Specifically moderate exercise was associated with a lower risk of prostate cancer and in men with cancer, lower grade disease. Further investigation using an objective measure of exercise in a larger sample size is required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 20 publications
4
37
0
1
Order By: Relevance
“…Our population represents patients at high risk for prostate cancer (elevated PSA and/or abnormal DRE) and thus may not be generalizable to all men at risk of prostate cancer. Moreover, we did not assess information on physical activity or diet, which are associated with DM, risk of prostate cancer, and potentially cancer grade at diagnosis (Antonelli et al, 2009). Finally, given DM is associated with other diseases and patients with DM usually receive specific therapeutic interventions (e.g., insulin therapy) and these data were also unavailable for all patients, we were not able to control for these potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Our population represents patients at high risk for prostate cancer (elevated PSA and/or abnormal DRE) and thus may not be generalizable to all men at risk of prostate cancer. Moreover, we did not assess information on physical activity or diet, which are associated with DM, risk of prostate cancer, and potentially cancer grade at diagnosis (Antonelli et al, 2009). Finally, given DM is associated with other diseases and patients with DM usually receive specific therapeutic interventions (e.g., insulin therapy) and these data were also unavailable for all patients, we were not able to control for these potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show that physically active prostate cancer patients have significantly greater quality of life 33,34 , less fatigue 35 , lower PSA levels 36 and can delay initiating ADT two years longer than their less-active prostate cancer peers 37 . Physically active prostate cancer patients also have significantly lower serum insulin and insulin-like growth factor (IGF-1), higher insulin-like growth factor binding protein (IGFBP-1) and a lower risk of high grade disease (Gleason score 7 or greater) compared to less-active prostate cancer patients [38][39][40] . Exercise is relatively inexpensive compared to pharmacological and/or radiation approaches 1 and has a social aspect that is important for older adults 41,42 and those with cancer 43,44 .…”
Section: Insert Figurementioning
confidence: 99%
“…The details of the case-control study have been previously reported (Antonelli et al, 2009). In brief, male patients from the Durham Veterans Affairs Medical Center (DVAMC) in Durham, North Carolina, who were undergoing a prostate needle biopsy between January 2007 and July 2010, were recruited to enroll in a hospital-based, prostate cancer casecontrol study.…”
Section: Study Populationsmentioning
confidence: 99%